Microbiological status of ice cream and tamarind juice (tok) collected from various locations of Dhaka city - Farah-Tuz, Mumu (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.